Rhythm and will in Victorian poetry - Campbell, Matthew (Matthew J. B.) (Cambridge studies in nineteenth-century literature and culture, 1999)
"In Rhythm and Will in Victorian Poetry, Matthew Campbell explores the work of four Victorian poets - Tennyson, Browning, Hopkins and Hardy - as they show a consistent and innovative concern with questions of human agency and will. The Victorians saw the virtues attendant upon a strong will as central to themselves and to their culture, and Victorian poetry strove to find an aesthetic form to represent this sense of the human will. Through close study of the metre, rhyme and rhythm of a wide range of poems - including monologue, lyric and elegy - Campbell reveals how closely technical questions of poetics are related, in the work of these poets, to issues of psychology, ethics and social change. He goes on to discuss more general questions of poetics, and the implications of the achievement of the Victorian poets in a wider context, from Milton through Romanticism and into contemporary critical debate."--Jacket